Dietary broccoli protects against fatty liver development but not against progression of liver cancer in mice pretreated with diethylnitrosamine - Chen, Yung-Ju (J Funct Foods, 2016)
Western-style high fat, high sugar diets are associated with non-alcoholic fatty liver disease (NAFLD) and increased liver cancer risk. Sulforaphane from broccoli may protect against these. Previously we initiated broccoli feeding to mice prior to exposure to the hepatocarcinogen diethylnitrosamine (DEN), and saw protection against NAFLD and liver cancer. Here we administered DEN to unweaned mice, initiating broccoli feeding two weeks later, to determine if broccoli protects against cancer progression. Specifically, male 15-day-old C57BL/6J mice were given DEN and placed on a Western or Western+10%Broccoli diet from the age of 4 weeks through 7 months. Dietary broccoli decreased hepatic triacylglycerols, NAFLD, liver damage and tumour necrosis factor by month 5 without changing body weight or relative liver weight, but did not slow carcinogenesis, seen in 100% of mice. We conclude that broccoli, a good source of sulforaphane, slows progression of hepatic lipidosis, but not tumourigenesis in this robust model.